Effect of Quinoline Substitution on Water Oxidation by [Ru(Ql–tpy)(bpy)(OH2)](PF6)2. Issue 10 (7th April 2017) - Patel, Jully; Majee, Karunamay; Raj, Manaswini; Vatsa, Aditi; Rai, Surabhi; Padhi, Sumanta Kumar
Abstract: The new ligand Ql‐tpy (8‐(2, 6‐di(pyridin‐2‐yl)pyridin‐4‐yl)quinoline) and the corresponding aqua complex [Ru(Ql‐tpy)(bpy)(OH2 )](PF6 )2 (1 ) have been synthesized and characterized by the different spectroscopic methods. This complex shows two pKa values, pKa 1 due to the deprotonation from the protonated N atom located on the quinoline moiety at 3.0 and another pKa 2 at 10.5 due to the deprotonation from aqua ligand. The catalytic activity of the complex1 towards water oxidation was studied in CF3 SO3 H solution (pH ≈ 1) using Ce IV as an oxidant. The free N atom of the substituted quinoline moiety of the complex gets protonated at pH ≈ 1 and acts as an electron withdrawing group instead of electron donating group. Due to the electron withdrawing effect it shows a lower catalytic activity towards chemical water oxidation having turnover number (TON) of 18 (out of 25) and initial turnover frequency (TOF) 0.003 s −1 as compared to the previously reported [Ru II (QCl‐tpy)(bpy)(H2 O)] 2+ complex. Abstract : The mononuclear complex [Ru(Ql‐tpy))(bpy)(OH2 )] 2+, has been synthesized and it's catalytic studies towards water oxidation in presence of Ce IV as an oxidant, have been demonstrated. The terminal quinoline moiety behaves as an electron withdrawing group towards catalytic effect.